2021
DOI: 10.1001/jamanetworkopen.2021.28176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Population-Level Changes Associated With the 2021 US Preventive Services Task Force Lung Cancer Screening Recommendations in Community-Based Health Care Systems

Abstract: IMPORTANCEThe US Preventive Services Task Force (USPSTF) released updated lung cancer screening recommendations in 2021, lowering the screening age from 55 to 50 years and smoking history from 30 to 20 pack-years. These changes are expected to expand screening access to women and racial and ethnic minority groups. OBJECTIVETo estimate the population-level changes associated with the 2021 USPSTF expansion of lung cancer screening eligibility by sex, race and ethnicity, sociodemographic factors, and comorbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…In 2021, the US Preventive Services Task Force updated their lung cancer screening guidelines by lowering both the age of initiation (from 55 to 50 years) and the packyear smoking history (from 30 to 20 pack-years), consistent with the eligibility criteria for the Multicentric Italian Lung Detection Trial, which found a 39% reduction in lung cancer mortality. 99,100 Although part of the impetus in the change was to attenuate racial and socioeconomic disparities in screening by capturing a larger proportion of Black people at elevated risk, 101 one modeling study found that disparities may widen without the prioritization of individuals with the highest benefit because of unequal dissemination of screening. 102 Survival has increased for patients with lung cancer over the past decade because of advancements in diagnostics, surgical procedures, and therapeutics.…”
Section: Tablementioning
confidence: 99%
“…In 2021, the US Preventive Services Task Force updated their lung cancer screening guidelines by lowering both the age of initiation (from 55 to 50 years) and the packyear smoking history (from 30 to 20 pack-years), consistent with the eligibility criteria for the Multicentric Italian Lung Detection Trial, which found a 39% reduction in lung cancer mortality. 99,100 Although part of the impetus in the change was to attenuate racial and socioeconomic disparities in screening by capturing a larger proportion of Black people at elevated risk, 101 one modeling study found that disparities may widen without the prioritization of individuals with the highest benefit because of unequal dissemination of screening. 102 Survival has increased for patients with lung cancer over the past decade because of advancements in diagnostics, surgical procedures, and therapeutics.…”
Section: Tablementioning
confidence: 99%
“…This gap is expected to close with the new approved USPSTF 2021 LC screening guidelines, 15 which could potentially capture an additional 18 533 eligible individuals. 11 Such impact was seen in our subanalysis, which found significantly increased eligibility rates when implementing USPSTF21 compared to the USPSTF13. However, as it has been described in the literature, eligibility is not equally proportionate to individuals screened.…”
Section: Discussionmentioning
confidence: 58%
“…This is thought to be promising for high-risk patients and its recommendation was also adapted by organizations including the American Cancer Society. 11 , 12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, wider screening was associated with an estimated 30% increase in lung cancer diagnosis. 1…”
mentioning
confidence: 99%